The Likeability Penalty in Leadership : Decision-Making and Authority Challenges for Women - Kim, Anastasiya (2025)
This master’s thesis investigates the “likeability penalty” and its influence on the decision-making behaviors and authority challenges experienced by women in middle to senior management positions. Using a qualitative, interpretivist approach, the research involved semi-structured interviews with eight female leaders across diverse corporate sectors. Thematic analysis reveals that women leaders acknowledge this penalty, yet with experience, often shift focus from likeability to respect and impact. Findings indicate distinct adaptive strategies, blending collaborative and situationally authoritative decision-making, underscored by rational justification. The study concludes that the likeability penalty shapes leadership behaviors and hinders career progression through internalized barriers, highlighting the need for inclusive organizational cultures and objective support systems to mitigate these challenges.